Identification of Metacognitive Regulation Difficulties in Polya's Problem Solving - Destia Wahyu Hidayati; Lenny Kurniati (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
The thought process is an activity that is carried out every day. The flow of thinking is a way of directing cognitive processes in solving problems. The ability to manage cognitive processes is metacognitive. The branch on metacognitive is metacognitive regulation. Metacognitive regulation and problem-solving ability have a linear relationship, so to increase problem solving ability, the step that can be used is to increase metacognitive regulation. The aim of the research is to identify difficulties in metacognitive regulation in students in the medium, low and high groups so that educators can overcome these difficulties so that problem solving abilities can be increased. This research is a qualitative research. The research subjects are students of Mathematics Education Department Ivet University. The data collection instruments were problem-solving ability test questions and interview guide sheets. Data collection techniques are tests and interviews. The data analysis technique is an analysis technique from Miles and Huberman. The data credibility technique used is technical triangulation. The research results obtained are the difficulty of metacognitive regulation on the indicators (a) determining the steps to be taken after understanding the problem, (c) making a settlement plan, (d) implementing the plan at the coherent implementation stage of the plan, (e) determining a more appropriate way of problem solving. Keywords: flow of thought, cognitive processes, metacognitive regulation, problem solving abilities.